Optimizing Transit Operations and Passenger Experience: A Simulation-based Study of Bus Interarrival and Passenger Load Scenarios at a Major Transfer Point - Liperda, Rahmad Inca; Fatahayu, Nafi Riska (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
This study employs simulation-based analysis of passenger flow and bus operations at the Adam Malik transfer point within the TransJakarta BRT system. The findings from the analysis of the current system indicate that the average number of total passenger exits in corridors 13, 13B, 13C, and L13E were 618, 509, 1143, and 790, respectively. Additionally, the average time spent by passengers within the system for each corridor was 4.48 minutes, 6.12 minutes, 5.94 minutes, and 5.46 minutes, respectively. Through the development of 15 scenarios, the study demonstrates the impact of adjusting passenger boarding procedures and reducing interarrival time on waiting times and passenger processing efficiency, particularly during peak hours. The results emphasize the substantial influence of these variables on waiting times, total exits, and system duration for passengers and buses.